PENGELOLAAN POS KESEHATAN DESA PONIKI KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - MOKOROWU, VINI VITALIA; PANGKEY, MASJE SILIJA; KOLONDAM, HELLY (Sam Ratulangi University, 2019)
Vilage health post is a community based health effort that serves as a forum for the health of rural communities. The purpose of this study was to find out how to manage the Village Health Post in Poniki Village. This study uses descriptive qualitative research methods. Data collection techniques used were observation, interviews, and data collection with documents to see how the management of Poskesdes in Poniki Village. This researcher uses four indicators, namely: planning, organizing, actuating, and controlling. Based on the results of research on the Village Health Post stated that the immature planning resulted in the Poskesdes not running according to their functions, there was no action from the Health Office to advance the Poskesdes in Poniki Village, and lack of supervision from the Health Office to each village health post. The village has many Poskesdes which until now have not run. It can the be said that the management of the Village Health Post in Poniki Village is still not good.Keywords: Management, Health Post, Village.